2013
DOI: 10.1097/ta.0b013e31828fa408
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Berlin definition in PROMMTT patients

Abstract: Introduction Acute lung injury following trauma resuscitation remains a concern despite recent advances. Utilizing PROMMTT study population, the risk of hypoxemia and potential modifiable risk factors are studied. Methods Patients with survival ≥ 24 hours with at least 1 ICU day were included in the analysis. Hypoxemia was categorized utilizing the Berlin definition for ARDS: none (PaO2 to FiO2 ratio (P/F) > 300 mmHg), mild (P/F = 201–300), moderate (P/F = 101–200) or severe (P/F ≤ 100). The cohort was dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Over the last decade, transfusion therapy has undergone a significant change with many patients receiving less crystalloid and early, more balanced transfusion ratios attempting to reconstitute whole blood. 412,27,3241 This change has largely been associated with decreased transfusion amounts, fewer inflammatory complications, and improved survival. 412,27,3241 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, transfusion therapy has undergone a significant change with many patients receiving less crystalloid and early, more balanced transfusion ratios attempting to reconstitute whole blood. 412,27,3241 This change has largely been associated with decreased transfusion amounts, fewer inflammatory complications, and improved survival. 412,27,3241 …”
Section: Discussionmentioning
confidence: 99%
“…412,27,3241 Recent trauma resuscitation studies have demonstrated that most early deaths due to hemorrhage occur within 2 to 3 hours. 3,10,27,50,51 The PROMMTT study demonstrated a median time to hemorrhagic death from admission of 2.6 hours, 10 and in the PROPPR trial, the median time was 2.3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing volumes of crystalloid, on the other hand, are associated inflammation (e.g. acute respiratory distress syndrome), 19 edema (e.g. abdominal compartment syndrome), 20 and mortality.…”
Section: Damage Control Resuscitation (Dcr)mentioning
confidence: 99%
“…97,98,99 Analysis of the prospectively-acquired PROMMTT dataset did not demonstrate an independent association between blood product use and moderate-to-severe hypoxemia. 37 Indeed, the PROPPR randomized trial found no difference in inflammatory or transfusion-related complications between the high and low ratio groups. 5 …”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 98%
“…35,36 Analysis of the PROMMTT dataset found that increasing crystalloid use was independently associated with moderate or severe hypoxemia. 37 …”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 99%